2003
DOI: 10.1063/1.1580099
|View full text |Cite
|
Sign up to set email alerts
|

Origin of particle clustering in a simulated polymer nanocomposite and its impact on rheology

Abstract: Many nanoparticles have short-range interactions relative to their size, and these interactions tend to be ''patchy'' since the interatomic spacing is comparable to the nanoparticle size. For a dispersion of such particles, it is not a priori obvious what mechanism will control the clustering of the nanoparticles, and how the clustering will be affected by tuning various control parameters. To gain insight into these questions, we perform molecular dynamics simulations of polyhedral nanoparticles in a dense be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
184
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(196 citation statements)
references
References 56 publications
12
184
0
Order By: Relevance
“…[10][11][12][13] The mechanism of cluster assembly is particularly relevant to polymer-NP composites, but has potential relevance for many fields, such as biological systems where molecular assembly often occurs in the "crowded" intracellular and extracellular environments. 14,15 Our study builds upon the observations made in an earlier study 16 on the factors controlling NP dispersion in polymer melts. From Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] The mechanism of cluster assembly is particularly relevant to polymer-NP composites, but has potential relevance for many fields, such as biological systems where molecular assembly often occurs in the "crowded" intracellular and extracellular environments. 14,15 Our study builds upon the observations made in an earlier study 16 on the factors controlling NP dispersion in polymer melts. From Ref.…”
Section: Introductionmentioning
confidence: 99%
“…From Ref. 16 it was found that the NP underwent a thermally reversible transition to a clustered state upon cooling, in lieu of ordinary phase separation from the polymer matrix. The clustering had characteristics similar to those of equilibrium polymerization [10][11][12][13]17,18 and micelle formation.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were some differences in scale between the simulated composite and the experimental data, qualitative similarities were noted in the shear behavior. Starr et al [2003] investigated the effect of particle clustering on the PNC rheological behavior. Systems with well-dispersed particles showed higher η, especially at lowγ, which increased with concentration (φ ≥ 0.15).…”
Section: Modeling Of Pnc Flowsmentioning
confidence: 99%
“…Most such theories and models use a coarse-grained perspective where simple micromechanical representations are used for the polymers and fillers, with their interactions represented by few coarse-grained parameters. Using such representations, theories and simulations based on PRISM, [16][17][18] self-consistent field approaches, [19][20][21][22] field-theoretic, 23 and molecular dynamics simulations [24][25][26] have addressed the equilibrium structure and phase behavior of mixtures of (mostly) spherical nanofiller units dispersed in homopolymers, polymer blends, and block copolymers. Despite these advances, a number of open issues relevant to PNCs still remain:…”
Section: Structure and Dispersion Characteristics Of Pncsmentioning
confidence: 99%